ANALISIS PERBANDINGAN METODE PENILAIAN PERSEDIAAN PADA TOKO SEMBAKO FITRI DI KECAMATAN WATUBANGGA - Saputra, Muh Wahyu; Sabarudin, Sabarudin; Bustang, Bustang (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze and compare inventory valuation methods used by Toko Sembako Fitri in Watubangga District. The research uses a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings show that the store has a simple organizational structure and performs inventory recording manually without the support of an accounting information system. Currently, the store uses the last purchase price method, which does not comply with PSAK No. 202 regarding inventory. This research compares three inventory valuation methods: the last purchase price, FIFO (First In First Out), and weighted average. The results show that the FIFO method yields an ending inventory value of Rp 2,346,000 and the lowest gross profit, while the weighted average method results in an ending inventory value of Rp 2,376,452 and a higher gross profit. Based on these findings, the weighted average method is recommended as it provides more stable inventory values and generates optimal profit, especially during fluctuating price conditions. Keywords: Inventory Valuation Method, FIFO, Weighted Average, Gross Profit, Toko Sembako Fitri